« Contre leurs violences sexistes, autodéfense féministe ! » À propos des stages d’autodéfense féministe et de ce qu’ils nous enseignent - Aurélia Léon (Genre, Sexualité et Société)
The practice of developing feminist self-defense courses has increased in France over the past decade. Based on field research both as a PhD student in sociology and as a protagonist engaged in the dissemination of feminist self-defense – this article focuses first on the participant experience and some of its characteristics: the event quality of the classes; their role in the participants identification as a “public”, as Dewey put it, and the position of suffering and acting in this experience, and the opportunities participant experience offers to express experiences of victimization. The article then looks at the process to understand the regularity of such effects. In doing so, the article sheds light on the teleological dimension of the training – which invites to join the feminist “inquiry” regarding gender-based violence which started in the 1970s – and the methodological connection between empowerment and somatic experimentation.